Accelerating plant DNA barcode reference library construction using herbarium specimens: improved experimental techniques. (28th April 2015) - Xu, Chao; Dong, Wenpan; Shi, Shuo; Cheng, Tao; Li, Changhao; Liu, Yanlei; Wu, Ping; Wu, Hongkun; Gao, Peng; Zhou, Shiliang
Abstract A well‐covered reference library is crucial for successful identification of species by DNA barcoding. The biggest difficulty in building such a reference library is the lack of materials of organisms. Herbarium collections are potentially an enormous resource of materials. In this study, we demonstrate that it is likely to build such reference libraries using the reconstructed (self‐primed PCR amplified) DNA from the herbarium specimens. We used 179 rosaceous specimens to test the effects of DNA reconstruction, 420 randomly sampled specimens to estimate the usable percentage and another 223 specimens of true cherries (Cerasus, Rosaceae) to test the coverage of usable specimens to the species. The barcode rbcLb (the central four‐sevenths of rbcL gene) and matK was each amplified in two halves and sequenced on Roche GS 454 FLX+. DNA from the herbarium specimens was typically shorter than 300 bp. DNA reconstruction enabled amplification fragments of 400–500 bp without bringing or inducing any sequence errors. About one‐third of specimens in the national herbarium of China (PE) were proven usable after DNA reconstruction. The specimens in PE cover all Chinese true cherry species and 91.5% of vascular species listed in Flora of China. It is very possible to build well‐covered reference libraries for DNA barcoding of vascular species in China. As exemplified in this study, DNA reconstruction and DNA‐labelled next‐generation sequencing can accelerate the construction of local reference libraries. By putting the local reference libraries together, a global library for DNA barcoding becomes closer to reality.